HISTORY OF ISLAMIC CIVILIZATION AND THOUGHT AND ITS RELEVANCE TO CONTEMPORARY ISLAMIC EDUCATION - Birrul Walidainy Ary (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Islamic civilization is one of the leading civilizations that has ever existed on earth besides the Roman civilization, Egyptian civilization, Mesopotamia, etc. The presence of civilization because there are thoughts, research and implementation of renewal. This Islamic civilization and thought progressed until the golden age and the decline that started from the time of the Prophet to the present. This research discusses the history of Islamic civilization and thought and analyzes its relevance to the development of contemporary Islamic education. The research design is qualitative research and the method used is library research through documentation data collection techniques. Furthermore, the data were analyzed using a descriptive analysis approach . The findings in this study that the historical path of back and forth civilization and Islamic thought is inseparable from the commitment and consistency of Muslims as historical actors in upholding and implementing Islamic teachings themselves, because Islam is not just a heavenly religion, but Islam that is carried out in a sincere manner will shape civilization. superior and rahmatan lil'alamin.